ANALISIS PROSPEK SARANG BURUNG WALET DI KABUPATEN SUMBAWA - Dwi Sutrisno, Deni; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 4 (2024): Vol.13.No.4. APRIL 2024 [248-306], 2024)
One of the biological natural resources that has many ingredients and has health benefits and contains glycoprotein and is rich in minerals such as amino acids, calcium, sodium, magnesium and potassium is the swallow or its Latin name (collocalia sp). This research was conducted with the aim of analyzing the feasibility of the wallet bird's nest business in Sumbawa Regency. This research uses a quantitative-qualitative approach with a population of 30 swiftlet nest breeders in Sumbawa Regency. The analysis technique used is descriptive statistics. Based on the results of the analysis that has been carried out, it shows that if the NPV value resulting from the present value is positive, which means that the NPV is > 0. The Net B/C value and the Gross R/C value in this research are above 1, then the swallow nest breeders in Sumbawa subdistrict worth running. From the selling price, variable costs and fixed costs of 30 swallow nest breeders in Sumbawa District, the BEP value is 7.04 kg with a monthly income of Rp. 67,037,954. Based on the results of the analysis, it shows that the swiftlet nest farming business using NPV, BC, RC and BEP analysis is declared feasible to continue. keyword : Business Feasibility, Swallow Nest, Investment Analysis